Day of the Week Effect dan Volatilitas Cryptocurrency pada Masa Pandemi Covid-19 - Robiyanto Robiyanto; Yahya Rechtiawan Djari (AFRE (Accounting and Financial Review), 2021)
The cryptocurrency market is a market that attracts researchers and investors because it is open every day. This can be seen by the anomalies that occur in the cryptocurrency market. This research uses cryptocurrencies with the largest market cap in 2020, namely Bitcoin, Ethereum, Tether, XRP, and Bitcoin cash as research objects. The data in this study uses daily returns for testing the day of the week effect and daily volatility on the cryptocurrencies under study. This study uses GARCH (1,1) to determine the day of the week effect and daily volatility in the cryptocurrency under study. The results of this study indicate that there is a day of the week effect and daily volatility in the cryptocurrency under study, and it does not move freely. This causes the cryptocurrency market to become an inefficient market. The patterns that occur can be exploited by investors as well as other research on the cryptocurrency under study. Investors can avoid days that have high volatility for example in Bitcoin which experiences high volatility on Fridays and Saturdays because it has a high risk as well. Investors are advised to be able to trade on Thursday for high returns and less risk.Â